A translational medicine approach to molecular psychiatry - Honer, W. G. (Die Psychiatrie, 2012)
The place of molecular medicine in psychiatry is rapidly evolving. Research findings appear with great frequency, but the integration and impact of molecular research into the clinical practice of psychiatry is negligible. The present paper uses a translational medicine framework to provide a critical review of the possibilities for molecular medicine in psychiatry, focused on schizophrenia as an example illness.
Keywords: Schizophrenia; molecular psychiatry; translational medicine; genomics